Micromechanical Coupled Study of Crack Growth Initiation Criterion in Pressure Vessel Steel - Rakin, M.; Sedmak, A.; Cvijovic, Z.; Zrilic, M.; Sedmak, S. (Проблемы прочности, 2004)
We present results of the combined design-theoretical investigation of the mechanism of crack growth at the onset of ductile fracture of NPP reactor pressure vessels. Micromechanical approach to the prediction of ductile fracture has been applied, according to which the volume fraction of voids in the deformed material is determined by finite-element method. On the basis of CT-specimen tests and known damage parameters, obtained on smooth spherical specimens, we obtained micromechanical criterion of crack growth initiation for ductile fracture.